Kemampuan Ekstrak Jamur Lingzhi dalam Menghambat a-Glucosidase dan Menurunkan Kadar Gula Darah pada Tikus Hiperglikemia (THE ABILITY OF LINGZHI MUSHROOM EXTRACT (GANODERMA LUCIDUM) IN INHIBITING a-GLUKOSIDASE AND ITS EFFECT ON HIPERGLYCEMIAOF RATS) - Indriani, Ratih Dwi; Suarsana, I Nyoman; Sudira, I Wayan (Jurnal Veteriner, 2015)
Lingzhi mushrooms has been widely used by community empirically for the traditional medicine forlowering blood glucose levels. The purpose of this study was to determine the ability of the lingzhimushroom (Ganoderma lucidum) extract to inhibit á-glukosidase hyperglycemia in rat. Lingzhi mushroomethanol-extract were tested for their inhibition against á-glucosidase using spectrophotometry method. Atotal of 25 rats used in this study were divided into five groups. Four groups of rats (P1-P4) were given 2 mlof sucrose 80% orally, and one group of rats (P0) as a negative control. Ten minutes before giving sucrose,three groups (P2-P4) of rats were given the lingzhi mushroom extract of 1 ml orally at a dose of 10%, 20%,and 30% respectively, while the second groups (P1) as a positive control of hyperglycemia. After that in allgroups were examined the blood glucose levels at 0, 10, 30, 60, 90, and 120 minute after sucroseadministration. The results showed, lingzhi mushroom extract has the ability to inhibit á-glucosidasewith IC50 value of 162,01 ìgmL-1. The result of blood glucose test showed that administration of lingzhimushroom extract at a dose of 30% faster lowering blood glucose levels compared with a dose of 10% and20%.
Keywords: lingzhi mushroom, sucrose solution, hyperglycemia, IC50